The Earth & Universe Augmented Reality Educational Book - Eh Phon, Danakorn Nincarean; Anis Farihan, Mat Raffei; Adzhar, Kamaludin; Noraniza, Samat; Nur Shamsiah, Abdul Rahman (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Students have been perceiving even simple concepts in science are particularly difficult to grasp, since many ideas involve three-dimensional thinking. So, an Augmented Reality learning tool was developed to provide easy-to-use teaching/learning tools for learners and educators. The unique capability that allows virtual objects to appear in real world can serve as an effective tool to facilitate students to acquire better understandings on science and assist teachers to teach concepts that cannot be easily seen in a natural environment. Thus, AR-SMB has a bright potential for expansion and among potential markets include schools, parents and collaboration with publisher like Sasbadi/Pelangi.